Complement system activation in ANCA vasculitis: A translational success story?. Issue 1 (November 2015) - Kallenberg, Cees G.M.; Heeringa, Peter
Abstract: The ANCA-associated vasculitides (AAV) are characterized by pauci-immune necrotizing small to medium size vessel vasculitis frequently including necrotizing crescentric glomerulonephritis. Neutrophil activation by ANCA appears a primary pathogenic event. More recently, the complement system has been shown to be involved as well. Activation of the alternative pathway of complement, at least in part via activated neutrophils, results, amongst others, in the generation of C5a, a strong chemoattractant for neutrophils. C5a is also effective in neutrophil priming, a process leading to surface expression of the ANCA antigens so enabling neutrophils to be further activated by ANCA. Both in vitro and in vivo experimental data and histopathological studies from AAV patients underscore the role of complement, and particularly of C5a, in the pathophysiology of AAV. Preliminary data show that blocking of the C5a-receptor is a promising approach in the treatment of AAV.